The Effect of Isoflavone in Cowpea (Vigna unguiculata) Powder Supplement on Post-Menopausal Vaginal Maturation Index at Malang, Indonesia - Tatik Sujiati; Budi Siswanto; A Hidayat; Ayu Rizky Widowati (Asian Journal of Health Research, 2022)
Background: Only a few published studies have directly demonstrated the effects of local soy isoflavone on the post-menopausal vaginal maturation index. This study focused on the effect of 24 weeks of local soy isoflavone (67,5 mg) consumption to improve the post-menopausal vaginal maturation index. Material and Methods: 50 post-menopausal women were randomly assigned to a double-blind clinical trial to receive cowpea (Vigna unguiculata) powder treatment (n=25) and placebo (n=23). Vaginal cytology (maturation index, maturation value) was evaluated at pre and post-treatment in Anatomy Pathology Laboratories. Collected data were analyzed by using the analysis of covariant (ANOVA) method. Result: There is no difference in maturation vaginal index between the treatment and the placebo group. The treatment was not significantly improved the vaginal maturation index (p<0,05). The concomitant variable, age, post-menopausal interval, BMI, marital status, and initial cell condition have no significant effect on the maturation vagina index. Conclusion: Cowpea powder supplement with 67,5 mg isoflavone cannot improve the vaginal maturation index on post-menopausal patients.